Propuesta para el desarrollo de zonas rurales andinas basadas en el turismo de experiencias: un caso de estudio de la comunidad de Santa Bárbara en el cantón Cotacachi, Ecuador (Estudios) - Benítez, Juan Patricio (2025)
The main objective of this study is to propose strategies that help the development of community tourism based on experiential tourism strategies in the community of Santa Bárbara in Cotacachi, Ecuador. The study was divided into two phases: the first comprised basic thematic research, including sociodemographic analysis and community perception; the second focused on the identification and ranking of tourist attractions. The results showed that the community has significant natural and cultural resources, but faces challenges such as poor diversification of services and lack of authentic tourist experiences. Strengths were identified in the community, such as the preservation of ancestral knowledge and community organization, but they also have weaknesses such as youth migration and lack of economic resources. The proposed strategies include actions to conserve natural resources, promote the Andean worldview, design authentic tourism experiences, and strengthen local governance. In conclusion, the implementation of sustainable tourism management practices is recommended to promote economic development, preserve cultural heritage, and minimize negative impacts on the environment, promoting the participation and collaboration of all actors involved.